(untitled) (Journal of Health, Population and Nutrition, 2011)
To examine how health caregivers in under-resourced South African settings select from among the healthcare alternatives available to them during the final illness of their infants. Qualitative interviews were conducted with 39 caregivers of deceased infants in a rural community and an urban township. Nineteen local health providers and community leaders were also interviewed to ascertain opinions about local healthcare and other factors impacting healthcare-seeking choices. The framework analysis method guided qualitative analysis of data. Limited autonomy of caregivers in decision-making, lack of awareness of infant danger-signs, and identification of an externalizing cause of illness were important influences on healthcare- seeking during illnesses of infants in these settings. Health system factors relating to the performance of health workers and the accessibility and availability of services also influenced healthcare-seeking decisions. Although South African public-health services are free, the findings showed that poor families faced other financial constraints that impacted their access to healthcare. Often there was not one factor but a combination of factors occurring either concurrently or sequentially that determined whether, when, and from where outside healthcare was sought during final illnesses of infants. In addition to reducing health system barriers to healthcare, initiatives to improve timely and appropriate healthcare-seeking for sick infants must take into consideration ways to mitigate contextual problems, such as limited autonomy of caregivers in decision-making, and reconcile local explanatory models of childhood illnesses that may not encourage healthcare-seeking at allopathic services. Key words: Healthcare; Healthcare-seeking behaviour; Infant mortality; Medicine, Traditional; Qualitative research; South Africa DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8455 JHPN 2011; 29(4): 379-387